Effect of carotenoids on cichlid phenotype and mating behavior. Issue 1 (2nd January 2016) - Sorensen, A.E.; Mellor, D.; Jordan, R.C.
Abstract : Carotenoids are suspected to be honest indicators of health and adaptation for some cichlid species. In this study, male and female Metriaclima zebra cichlid fishes were fed a specialized diet of carotenoids, and their phenotypic expression and behavioral changes were measured. The effect of carotenoids on female–male mate choice behavioral interactions was also measured. When males were fed either a high- or low-carotenoid diet there was no statistically significant difference in coloration. There was, however, a statistically significant difference in coloration when males were reared in social versus non-social conditions. In Metriaclima zebra cichlids, carotenoids do not appear to be an important factor for mate choice, but other rearing conditions may be.